DEVELOPMENT OF ARDUINO-BASED CIGARATTE SMOKE DETECTION DEVICE AT SMK NEGERI 2 MAKASSAR - Muliadi Muliadi; Muhammad Yusuf Mappeasse; Nursiah Nursiah (Jurnal Media Elektrik, 2024)
This research method is research and development which aims to produce and know the test results of the development of Arduino-based cigarette smoke detection devices at SMK Negeri 2 Makassar. This software system uses ISO 25010 using the system quality testing stage to obtain the results of functionality, usability, portability, Compatibility, Reliability, Security. This tool has been tested on 22 respondents. This tool has the potential to detect the presence of cigarette smoke or be used as a fire warning system. To improve the ability to detect cigarette smoke is to combine the Internet of Things (IoT) with the Arduino platform. The main components used in this system include Arduino, MQ7 sensor, Flame detector, NodeMCU ESP8266 module, Buzzer or speaker as audio alert, and electrical adapter. When smoke is detected past a predetermined threshold, this tool will issue a warning, both visual and audible, and send data through the Blynk application. In software reliability testing, we got 173 results from each coding and progress status is good or working which indicates the system has fulfilled the reliability aspect. For security testing using the OWSP ZAP application to determine vulnerability or security. As a result, the tool has a medium security level system, which states that the error rate on the server and coding (source code) in the application is categorized as safe